Mahonia lancasteri (Berberidaceae), a new species originating from Sichuan (China) described from cultivation - Colin, Olivier; Hinsinger, Damien Daniel; Strijk, Joeri Sergej (Phytotaxa, 2021)
Mahonia lancasteri (Berberidaceae) is described from cultivation as a new species from west-central Sichuan, China. A detailed description, distributional data and ecological information along with color photographs are provided. In addition, a comparison of M. lancasteri with morphologically similar species, as well as information about its introduction and history in cultivation, is presented. We also performed a phylogenetic analysis using five molecular loci (nuclear ITS, accD, ndhF, rbcL and psbA-trnH) to further determine the close affinities of M. lancasteri. The new species naturally occurs in sympatry with several other Mahonia species.